Research trends around open innovation in higher education: advancements and future direction - Valencia-Arias, Alejandro; Gómez-Bayona, Ledy; Moreno-López, Gustavo; Sialer-Rivera, Noelia; Bernal, Olga-Vélez; Gallegos, Ada; Arias-Vargas, Francisco Javier (Frontiers in Education, 2023)
Open innovation in higher education has emerged as a vital approach, especially in the context of the COVID-19 pandemic, to foster collaboration, knowledge exchange, and address challenges in the academic sector. This study investigates the impact of open innovation on entrepreneurial skills, value co-creation, and technology transfer barriers by examining collaborations between universities and industries in emerging economies and knowledge absorption in SMEs. Additionally, it underscores the significance of open innovation in enhancing teaching and learning quality and aligning with Sustainable Development Goals. To address research gaps, a bibliometric study using VOSviewer software is proposed, aiming to analyze co-occurrence between keywords and explore the relationships between variables. Following the PRISMA statement’s parameters for systematic literature review, the methodology ensures a comprehensive and replicable approach for accurate findings. The study reveals an increasing trend in literary production, with the United Kingdom and Spain leading academic progress. Prominent research trends include technology transfer through open innovation strategies, diversification of business models due to innovation policies, factors influencing collaboration between companies and universities, and the emergence of Education 4.0 with novel educational systems leveraging technology. These findings have implications for supporting the education sector, benefiting students, graduates, and the broader community.